2004
DOI: 10.1590/s1516-44462004000100015
|View full text |Cite
|
Sign up to set email alerts
|

Atualização sobre o tratamento neurocirúrgico do transtorno obsessivo-compulsivo

Abstract: Responses to pharmacotherapy and psychotherapy in obsessive-compulsive disorder (OCD) range from 60 to 80% of cases. However, a subset of OCD patients do not respond to adequately conducted treatment trials, leading to severe psychosocial impairment. Stereotactic surgery can be indicated then as the last resource. Five surgical techniques are available, with the following rates of global post-operative improvement: anterior capsulotomy (38-100%); anterior cingulotomy (27-57%); subcaudate tractotomy (33-67%); l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 15 publications
(17 reference statements)
0
15
0
6
Order By: Relevance
“…The specifics of each procedure are covered in other reviews in the area. 111,112 Currently, no published controlled studies have demonstrated the efficacy of neurosurgery for the treatment of OCD. Reviews of open studies of neurosurgical procedures in OCD have suggested 50–60% response rates observed after 6–24 months.…”
Section: Resultsmentioning
confidence: 99%
“…The specifics of each procedure are covered in other reviews in the area. 111,112 Currently, no published controlled studies have demonstrated the efficacy of neurosurgery for the treatment of OCD. Reviews of open studies of neurosurgical procedures in OCD have suggested 50–60% response rates observed after 6–24 months.…”
Section: Resultsmentioning
confidence: 99%
“…Among several tools that are based in the neuroanatomy, we can mention transcranial magnetic stimulation (TMS), vagus nerve stimulation (VNS) e deep brain stimulation (DBS), in addition to the well-known neurosurgical techniques. 55,56 1. Transcranial magnetic stimulation (TMS) According to the 2003 Cochrane Database Systematic Reviews, three clinical trials have been included in a review on TMS in OCD, and two of them included data that were adequate for the analysis, but did not allow the performance of a metaanalysis.…”
Section: Approaches Based On Brain Circuitsmentioning
confidence: 99%
“…Most of them are prospective follow-ups of one or more cohorts of patients who underwent surgery. 55 Only one randomized clinical trial of neurosurgery has been carried out, and it compared the capsulotomy to the cingulotomy, but with a small number of patients. 61 On the other hand, in DES studies of the internal capsule, we found randomized clinical trials, but they involved small samples.…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
See 2 more Smart Citations